Maternal and fetal cardiovascular responses to acute high-intensity interval and moderate-intensity continuous training exercise during pregnancy: a randomized crossover trial - Wowdzia, J. B.; Hazell, T. J.; Berg, E. R. V.; Labrecque, L.; Brassad, P.; Davenport, M. H. (Sports Medicine, 2023)
Objective: We aimed to compare maternal and fetal cardiovascular responses to an acute bout of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) during pregnancy. Methods: Fifteen women with a singleton pregnancy (27.3 ± 3.5 weeks of gestation, 33 ± 4 years of age) were recruited. Following a peak fitness test, participants engaged in a session of HIIT (10 × 1-min intervals = 90% maximum heart rate [HRmax]) interspersed with 1 min of active recovery) and MICT (30 min at 64-76% HRmax) 48 h apart in random order. Maternal HR, blood pressure, middle (MCAv), and posterior cerebral artery blood velocity (PCAv), as well as respiratory measures were monitored continuously throughout HIIT/MICT. Fetal heart rate, as well as umbilical systolic/diastolic (S/D) ratio, resistive index (RI), and pulsatility index (PI) were assessed immediately before and after exercise. Results: Average maternal heart rate was higher for HIIT (82 ± 5% HRmax) compared with MICT (74 ± 4% HRmax; p < 0.001). During the HIIT session, participants achieved a peak heart rate of 96 ± 5% HRmax (range of 87-105% HRmax). Maternal cerebral blood velocities increased with exercise but was not different between HIIT and MICT for MCAv (p = 0.340) and PCAv (p = 0.142). Fetal heart rate increased during exercise (p = 0.244) but was not different between sessions (HIIT: ? + 14 ± 7 bpm; MICT: ? + 10 ± 10 bpm). Metrics of umbilical blood flow decreased with exercise and were not different between exercise sessions (PI: p = 0.707; S/D ratio: p = 0.671; RI: p = 0.792). Fetal bradycardia was not observed, and S/D ratio, RI, and PI remained within normal ranges both before and immediately after all exercise sessions. Conclusions: An acute bout of HIIT exercise consisting of repeated 1-min near-maximal to maximal exertions, as well as MICT exercise is well tolerated by both mother and fetus.